STABILIZATION OF FEMORAL SHAFT FRACTURES BY INTERLOCKING INTRA MEDULLARY NAILING - DR.S.VARUN REDDY,; DR.G.KISHORE ROY, (International Journal of Pharma and Bio Sciences, 2014)
Femoral shaft fractures most often will be the result of high energy trauma in young adults.Surgical stabilization of the femoral shaft is the gold standard in their management worldwide. The pioneering work on intra-medullary nailing by Gerhard Kuntscher has revolutionized the management of femoral shaft fractures. Intra-medullary nailing being close to center of femur can tolerate bending and torsional loads better than plates. Closed nailing provides biological fixation. In the present study we would like to share our observations on the outcome of diaphyseal fractures of femur in adults treated with IM Interlocking nail. This is a prospective study of 30 adult patients with diaphyseal femoral shaft fractures treated with IM Interlocking nail. After a thorough pre-operative assessment cases were taken up for surgery. All the patients were assessed radiologically and clinically for fracture union at regular intervals of 6 weeks, 12 weeks and 1 year by using Thoreson’s criteria.The functional outcome was excellent in 23 cases, good in 5 cases, fair in 1 case and poor in 1 case. All the patients completed the study period. Closed IM interlocking nailing for femoral diaphyseal fractures provides biological fixation and good clinical outcome. IM nailing holds a good place in treating femoral diaphyseal fractures especially those with high comminution, long spiral and segmental fractures.